Synthesis of Novel Pyrano[2, 3‐b]pyridines from α, α′‐Bis(substituted‐benzylidene)cycloalkanones. (18th May 2013) - Bigdeli, Mohammad Ali; Marjani, Katayon; Farokhi, Elinaz; Sheikhhosseini, Enayatollah; Ghazanfari, Dadkhoda
<x xml:space="preserve">Abstract</x> In this paper, we describe a two‐step synthesis of a series of tacrine analogues. In the first step, α, α'‐bis(substituted‐benzylidene)cycloalkanones are reacted with malononitrile to afford 2‐amino‐3‐cyano‐4H‐pyrans. The second step involves the conversion of pyrans to pyrano[2, 3‐b]pyridines with the use of AlCl3 as catalyst.